'Say Ahhh': What do dentists, general medical practitioners and community pharmacists do about halitosis?. (19th December 2018) - Lau, Phyllis; Meethal, Chythra; Middleton, Michelle; Clark, Malcolm; Darby, Ivan
Abstract : Introduction: Halitosis is common and can have significant impact on quality of life. Current literature recommends multidisciplinary approaches. This paper explored the practice, knowledge and views of Australian general dental practitioners (GDPs), general medical practitioners (GMPs) and community pharmacists (CPs) on halitosis and interprofessional collaboration to manage halitosis. Methods: A mixed methods approach was used. Recruited GMPs, GDPs and CPs completed an online survey. A small number then participated in semi‐structured follow‐up interviews. Results: Sixty‐six GDPs, 27 GMPs and 114 CPs completed the survey. Five from each group were interviewed. Sixty‐eight percent of GMPs and 46% of CPs considered halitosis management part of their role despite the majority feeling that they had insufficient oral health training. Sixty‐eight percent of GMPs, 86% of GDPs and 79% of CPs thought interprofessional halitosis care would benefit patients. Most participants admitted to feeling uneasy when starting conversations with their patients about halitosis. Most GDPs did not monitor their patients' progress, and GMPs seemed comfortable in managing halitosis only when it had a systemic cause. Critically, the role of CPs in halitosis management was poorly understood. Conclusion: Most GDPs, GMPs and CPs find it challenging to manage patients with halitosis and are interested in working together. Improving health professionals' knowledge and training will contribute to comprehensive interprofessional halitosis management.